Duokines: a novel class of dual-acting co-stimulatory molecules acting in cis or trans. (2nd September 2018) - Fellermeier-Kopf, Sina; Gieseke, Friederike; Sahin, Ugur; Müller, Dafne; Pfizenmaier, Klaus; Kontermann, Roland E.
ABSTRACT: Co-stimulatory signals induced by ligands of the tumor necrosis factor superfamily (TNFSF) play a central role in T cell activation and have emerged as a promising strategy in cancer immunotherapy. Here, we established a novel class of bifunctional co-stimulatory fusion proteins with the aim to boost T cell activation at the level of T cell – antigen-presenting cell (APC) interaction. These novel dual-acting cytokine fusion proteins were created by connecting two different homotrimeric TNFSF ligands to form homotrimeric bifunctional molecules (Duokines) or by connecting single-chain derivatives of two different homotrimeric TNFSF with a single, flexible linker (single-chain Duokines, scDuokines). By linking the TNFSF ligands 4-1BBL, OX40L and CD27L in all possible combinations, cis-acting Duokines were generated that act on the same or adjacent T cells, while combining CD40L with 4-1BBL, OX40L and CD27L resulted in trans-acting Duokines acting simultaneously on APCs and T cells. In vitro, co-stimulation of T cells was seen for cis- and trans-acting Duokines and scDuokines in an antigen-independent as well as antigen-specific setting. Trans-acting molecules furthermore activated B cells, which represent a subclass of APCs. In a pilot experiment using the syngeneic B16-FAP mouse tumor model scDuokines displayed antitumoral activity in vivo in combination with a primary T cell-activating bispecific antibody, evident from reduced number of lung metastasis compared to the antibody-only treated group. Our data show that the bifunctional, co-stimulatory duokines are capable to enhance T cell-mediated anti-tumor immune responses, suggesting that they can serve as a new class of immuno-stimulatory molecules for use in cancer immunotherapy strategies.